Adaptación y rendimiento de cuatro variedades de trigo (Triticum aestivum L.) con dos fertilizantes químico y orgánico; en Salache Bajo- Latacunga -provincia de Cotopaxi 2015 - Herrera Galarza, Tania Fernanda (2017)
The country imports annually about 624 000, representing about 98% of domestic consumption. As mentioned, it was necessary to consider the research Adaptation and yield of four wheat varieties (Triticum aestivum L.) with two chemical and organic fertilizers; In Salache Bajo- Latacunga -Protocia de Cotopaxi 2015. Its specific objectives were: to identify which of the four wheat varieties (Triticum aestivum L.) is adapted in the locality; Determine the effect of both fertilizers and yield on different varieties. Carry out a cost / benefit analysis. The wheat varieties were obtained from the Seed Bank of the Technical University of Cotopaxi. These were INIAP Mirador 2010; INIAP San Jacinto 2010; INIAP Cojitambo 92; INIAP Vivar 2010; They were fertilized at 10-30-10 + Urea and organic fertilizer EcoAbonaza dosed according to the soil analysis and the requirement of the crop with a control. A completely randomized block design (DBCA) was used in a factorial arrangement of 4 x 3 x 3. In the research, no statistical significance was determined in their interaction A x B, whereby each factor studied is independent of the adaptation and productivity of wheat. The variety that showed the best agronomic characteristics was the variety INIAP Mirador 2010, with the highest emergency percentage of 75.56%; Number of spikelets / spike with 101.44; Length of 10 cm spike. And culture yield 1414.97 kg. The highest profit / cost ratio of 1.40 USD. It was with INIAP Mirador 2010, fertilized with chemical fertilizer.